Sheikh Al-Islam Ibn Taymiyyah's position from the doctrinal opinions: Imam Ibn Hazm as a model – A descriptive analytical study through the book of Majmoo' Al-Fataawa by Ibn Taymiyah - Al-Maliki, Safar Reda (Journal of Islamic Sciences, 2020)
The current study aims to identify the issues of jurisprudence in which Ibn Taymiyyah Ibn Hazm disagreed and know the point of disagreement, and to achieve the opinions and trends mentioned by Ibn Taymiyyah, and to devise the approach of Ibn Hazm and the extent of their compatibility and differences. To achieve the study the researcher used the descriptive-analytical method by recalling the issues and the way ibn Taymiyyah responded to the issues in which they agreed or disagreed with Ibn Hazm, and the study showed several results was The most important are
Keywords: Ibn Taymiyyah; Ibn Hazm; Virtual; Total Fatwas